Determining Factors Analysis of Traders in Taking Financing at KSPPS BMT Ben Sejahtera KCU Kroya - Nur Diana, Azka; Sulistiowati, Ani Retno; Hidayat, Ma'ruf (Wealth: Journal of Islamic Banking and Finance, 2023)
KSPPS BMT Ben Sejahtera KCU Kroya is the main branch office which is in the same location as the KSPPS BMT Ben Sejahtera Kroya head office, so when compared to other branch offices, of course BMT Ben Sejahtera Kroya has more complete services. However, in practice there are not a few problems encountered, namely the trader's decision to use financing products which results in the number of members of the financing realization experiencing instability every month. This study aims to determine whether cultural factors, social factors, personal factors and psychological factors influence traders' decisions in making financing at KSPPS BMT Ben Sejahtera KCU Kroya. This research uses quantitative methods. The population is traders who take financing from KSPPS BMT Ben Sejahtera KCU Kroya in 2021. The number of samples used is 60 respondents. The sampling technique uses Nonprobability Sampling by Purposive Sampling. The results showed that the variables of cultural factors and social factors partially had no effect on traders' decisions in making financing at KSPPS BMT Ben Sejahtera KCU Kroya. Meanwhile, personal factor variables partially have a negative effect on traders' decisions in making financing at KSPPS BMT Ben Sejahtera KCU Kroya. psychological factor variables partially influence traders' decisions in making financing at KSPPS BMT Ben Sejahtera KCU Kroya. Variable cultural factors, social factors, personal factors and psychological factors simultaneously influence traders' decisions in making financing at KSPPS BMT Ben Sejahtera KCU Kroya. Keywords: Cultural Factors, Social Factors, Personal Factors, Psychological Factors.